Innovative assembly strategy contributes to understanding the evolution and conservation genetics of the endangered Solenodon paradoxus from the island of Hispaniola. Issue 6 (16th March 2018) - Grigorev, Kirill; Kliver, Sergey; Dobrynin, Pavel; Komissarov, Aleksey; Wolfsberger, Walter; Krasheninnikova, Ksenia; Afanador-Hernández, Yashira M; Brandt, Adam L; Paulino, Liz A; Carreras, Rosanna; Rodríguez, Luis E; Núñez, Adrell; et al.
Abstract: Solenodons are insectivores that live in Hispaniola and Cuba. They form an isolated branch in the tree of placental mammals that are highly divergent from other eulipothyplan insectivores The history, unique biology, and adaptations of these enigmatic venomous species could be illuminated by the availability of genome data. However, a whole genome assembly for solenodons has not been previously performed, partially due to the difficulty in obtaining samples from the field. Island isolation and reduced numbers have likely resulted in high homozygosity within the Hispaniolan solenodon ( Solenodon paradoxus ). Thus, we tested the performance of several assembly strategies on the genome of this genetically impoverished species. The string graph–based assembly strategy seemed a better choice compared to the conventional de Bruijn graph approach due to the high levels of homozygosity, which is often a hallmark of endemic or endangered species. A consensus reference genome was assembled from sequences of 5 individuals from the southern subspecies ( S. p. woodi ). In addition, we obtained an additional sequence from 1 sample of the northern subspecies ( S. p. paradoxus ). The resulting genome assemblies were compared to each other and annotated for genes, with an emphasis on venom genes, repeats, variable microsatellite loci, and other genomic variants. Phylogenetic positioning and selection signatures were inferred based on 4, 416 single-copy orthologs from 10 other mammals. We estimated that solenodons diverged from other extant mammals 73.6 million years ago. Patterns of single-nucleotide polymorphism variation allowed us to infer population demography, which supported a subspecies split within the Hispaniolan solenodon at least 300 thousand years ago.